Examining blood-based biomarkers in prediction of cognitive deficits after mild traumatic brain injury - Kartio, Aura (My University, 2023)
Objective: The purpose of this study was to investigate if admission levels of total tau (T-tau), Interleukin-10 (IL-10), heart-fatty acid binding protein (H-FABP), neurofilament light (NFL), glial fibrillary acidic protein (GFAP) or β-amyloid isoforms 1-40 (Aβ40) and 1-42 (Aβ42) in blood could predict cognitive outcome after mild traumatic brain injury (mTBI). Methods: A total of 93 patients with mTBI [Glasgow Coma Scale (GCS) ≥ 13] recruited in Turku University Hospital, Turku, Finland were included in this study. Blood samples were drawn within 24 h of admission for analysis of the earlier mentioned biomarker levels. Patients were divided into computed tomography (CT)-positive and CT-negative groups. The functional outcome was assessed 4-17 months after the injury using the Extended Glasgow Outcome Scale (GOSE). The patients were then further divided into groups of complete (GOSE 8) and incomplete (GOSE < 8) recovery. The cognitive outcome was assessed 4-17 months after the injury using The Cambridge Neuropsychological Test Automated Battery (CANTAB). The correlation between the CANTAB scores and admission biomarker levels were analyzed both separately in above groups as well as using the whole cohort. The results were corrected for age and gender. Final results were corrected for multiple comparison. Differences in the CANTAB test results between the CT-positive and CT-negative groups as well as the groups of complete and incomplete recovery were tested to evaluate the overall predictive value of CANTAB scores in mTBI. Results: Significant correlations were found between Aβ42 levels and Simple Reaction Time, Standard Deviation of correct latency and Simple Reaction Time, Maximum correct latency in patients with complete recovery. Such correlations were not found in other groups or when the whole cohort was included in the tests. There were no other significant correlations found between the different biomarker levels and CANTAB test results. When comparing the CANTAB test results between groups, there was a significant difference in the Cambridge Gambling Tasks Deliberation time between the CT-positive and CT-negative patients. This difference was not found between incomplete and complete recovery-groups. There were no significant differences found in other CANTAB subdomains. Conclusion: In previous studies, there have been promising results when examining the prediction abilities of different biomarkers in TBI. However, none of the most studied TBI-related biomarkers (S100B, AB40, AB42, t-tau, GFAP, H-FABP, NFL and IL-10) alone can reliably predict a decrease in cognitive functions in patients with mTBI. However, when testing the differences in the CANTAB test results between different groups, a significant difference was found only in one CANTAB subdomain. This suggests that the CANTAB-test might not be specific enough to detect the cognitive long-term symptoms after mTBI.
Keywords: traumatic brain injury, blood biomarkers, outcome, cognition